Getting ahead, falling behind and standing still. Income mobility in Chile - Castro, Rodrigo (Estudios de Economía, 2016)
This paper analyses household income mobility in Chile between 1996 and 2001. Compared to industrialized and most developing countries, mobility has been quite high. The purpose of this paper is to apply a binomial probit model and split analysis into assessment of individuals and households on the relative income distribution. Main results are that moving from unemployment to employment significantly increases probability of moving up and decreases probability of moving down. Technical-professional education is promoting move up on the relative income scale and it is protecting movement down. An important result is that high-school education decreases probability of degradation.